Regional sea-level highstand triggered Holocene ice sheet thinning across coastal Dronning Maud Land, East Antarctica - Yusuke Suganuma; Heitaro Kaneda; Martim Mas e Braga; Takeshige Ishiwa; Takushi Koyama; Jennifer C. Newall; Jun’ichi Okuno; Takashi Obase; Fuyuki Saito; Irina Rogozhina; Jane Lund Andersen; Moto Kawamata; et al. (Communications Earth & Environment, 2022)
Regional sea-level highstand triggered rapid Holocene upstream thinning of the East Antarctic Ice Sheet in Dronning Maud Land, suggest ice sheet and crustal rebound model simulations constrained by cosmogenic nuclide chronometry.